Moderation effects of multiple directorships on audit committee and firm performance: A middle eastern perspective - Kamilah Kamaludin; Sheela Sundarasen; Izani Ibrahim (Cogent Business & Management)
This study examines the moderation effects of audit committee members’ multiple directorships on the association between the number of audit committee meetings, attendance in the audit committee meetings and firm performance. A panel generalized least square method is used as the analysis tool, on the selected listed firms in the Saudi Arabian Stock Market (Tadawul). Empirical evidence suggests an inverse relationship between the number of audit committee meetings, audit committee meetings’ attendance and firm performance. As for the moderation effects of multiple directorships, a positive effect is documented. The results indicate that the multiple directorships by the audit committee members play a significantly positive role on firm performance in the Kingdom of Saudi Arabia (KSA). This study underwrites a middle eastern perspective on the relationship between the number of audit committee meetings and its attendance and the moderation effects of audit committee members’ multiple directorships on firm performance. The findings of this study provide valuable insights to policymakers and practitioners. The results should provide support to regulatory authorities to legislate effective regulations to make internal governance mechanisms work more effectively in the country.